Comparative Analysis of 95 Patients with Different Severity in the Early Outbreak of COVID-19 in Wuhan, China - Fang He; Xue-feng Ding; Meng Cao; Hai-ying Gong; Xiang-zhen Fu; Jie Luo; Kui Liu; Zhou-zhou Tian; Lin Luo; Yu-yuan Fan; Ting Li; Qian-Jing Yao; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. To explore the clinical characteristics of patients with different severity in the early outbreak of COVID-19, hoping to provide reference for clinical diagnosis and treatment. Methods. We retrospectively analyzed the clinical data of 95 COVID-19 patients in Wuhan Red Cross Hospital of China from January 17 to February 13, 2020. All patients were investigated with epidemiological questionnaires. Outcomes were followed up until April 1, 2020. Results. There were 53 males and 42 females, aged 22–84 years (mean 57.3 years). Clinical classification included 54 cases of common type, 27 cases of severe type, and 14 cases of critical type. Six patients had been exposed to the local Huanan seafood market. There were 38 clusters of COVID-19, including 27 family clusters and 11 work unit clusters. Common symptoms included fever (86 (90.5%) of 95), cough (73 (76.8%)), and fatigue (50 (52.6%)). Laboratory findings showed that the most common abnormalities were lymphopenia (75 (78.9%)), elevated D-dimer (60 (63.2%)), and elevated C-reactive protein (56 (58.9%)) on admission. All patients had abnormal chest computed tomography, showing patchy shadows or ground-glass opacities. Severe and critical cases were older, more likely to have shortness of breath, more likely to have underlying comorbidities, and more likely to have abnormal laboratory findings than common cases. The prognosis of patients with different degrees of severity was significantly different. All common and severe patients (100%) were cured and discharged from the hospital, while 10 (71.4%) of 14 critical patients died. Conclusions. COVID-19 has fast transmission speed and high pathogenicity. We must assess the severity of the disease and take corresponding treatment measures as early as possible.